PENGEMBANGAN KONFIGURASI HOTSPOT DAN VOUCHER LOGIN MENGGUNAKAN MIKROTIK RB952ui DENGAN WEB TOP UP (STUDI KASUS : NORALONA COFFEE ROASTERY) - Indra Romadon (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2020)
The current internet access needs are very high, both to find the latest information, articles and seek entertainment. There are several places that provide internet access, one of which is a coffee shop. Many coffee shops implement Wi-fi facilities as a service to attract customers. Noralona Coffee and Roastery is a coffee shop located in the city of Cirebon that provides Wi-fi facilities for its customers. Wi-fi facilities available at the coffee shop have not restricted user access to the internet. One of them uses a hotspot and the calculation of hotspot access is done using a voucher system. Hotspot with this voucher system will be configured with MikroTik. On the proxy there is a hotspot service feature, then there are additional features, namely User Manager, which is a web interface for hotspot management. Vouchers are calculated based on time. and each voucher can be used by 1 user. This study aims to produce hotspot vouchers that can be topped up through the hotspot login website to make it easier for consumers to use Wi-fi, do top ups and reduce the use of ¬ Wi-fi that is too long for each visitor. The results of this study indicate that in a time-limited and user-vouched test, users cannot log in if the voucher is being used by 1 user, and if the voucher deadline has expired, the voucher can be Top Up again and consumers can only Top Up 1x voucher in a day. Keywords : Hotspot, Voucher, User Manager, Web Top Up, Top Up Voucher